Boater Compliance with Speed Regulations in High-Risk Areas for Marine Turtle Watercraft Strikes - Mariana M. P. B. Fuentes; Jessica Z. D’Auria; Stephanie Viegas Gkionis; Camille Kynoch; Joshua C. Manning; Sophie Mills; Sophie Rosengarten; Julia Saltzman; Armando Barsante Santos; Allen M. Foley (Coastal Management, 2026)

Examining Explicit Stereotype Perceptions of Colorectal Cancer Screening and Diagnosis in the Hispanic Community - Aidan Foley; Bianca Luna-Lupercio; Jessica M. Capaldi; Galen Wiens-Cook; Vinicius Calsavara; Zulfikarali Surani; Sarah-Jeanne Salvy; Jane C. Figueiredo; Robert Haile; Nenette A. Cáceres; Celina H. Shirazipour (Journal of Cancer Education, 2025)
Cancer is a leading cause of death among Hispanic people in the USA. One potential reason is low adherence to cancer screening guidelines, particularly for colorectal cancer (CRC). Previous research suggests that low CRC screening may be linked to negative stereotypes associated with cancer and CRC screening methods. The purpose of this study was to examine explicit stereotype perceptions of CRC screening and diagnosis in the Hispanic community. Hispanic adults ( n = 279) were asked to read three vignettes presenting a gender-neutral individual who was either diagnosed with CRC, completed colonoscopies for CRC screening, or was a control (no cancer information provided). Using the Stereotype Content Model approach, after reading each vignette, participants completed measures assessing explicit perceptions (warmth and competence) of the individual. Linear mixed-effects models were fitted to evaluate differences in perceptions between vignettes. The main effect indicated no significant difference in warmth or competence perceptions based on vignette condition ( p = .78). However, there was a significant difference in explicit perceptions based on the study participant’s Hispanic heritage, gender, and age ( p s < .05). Findings emphasize differences in explicit perceptions of cancer and cancer screening based on important demographic characteristics. Thus, important implications include the need for cancer educational materials and interventions to consider the important heterogeneity within the Hispanic community. Future CRC screening interventions should be tailored based on Hispanic heritage, gender, and age.

Deconstructing Protein in the Diet and Biomass of Colobine Primates - Katarina D. Evans; William J. Foley; Colin A. Chapman; Jessica M. Rothman (International Journal of Primatology, 2021)

Open science and meta‐analysis allow for rapid advances in ecology: A response to Menegotto et al. (2019) - Nicole L. Kinlock; Lisa Prowant; Emily M. Herstoff; Catherine M. Foley; Morodoluwa Akin‐Fajiye; Nicole Bender; Mihir Umarani; Hae Yeong Ryu; Bilgecan Şen; Jessica Gurevitch (Global Ecology and Biogeography, 2019)
Menegotto and colleagues’ (2019) commentary on our paper (Kinlock et al., 2018) does not negate our findings, but by recategorizing and reanalysing a portion of our data set, advances our knowledge of the latitudinal diversity gradients (LDGs) in marine ecosystems, particularly emphasizing different findings for benthic LDGs as a result of the recategorization of the data. Furthermore, we see the contribution by Menegotto et al. (2019) as highlighting the importance of scientific transparency; we believe that this insight into the nature of LDGs in marine systems would have been delayed, if not unobtainable, had we not provided fully transparent methods and complete data in our paper.

Explaining global variation in the latitudinal diversity gradient: Meta‐analysis confirms known patterns and uncovers new ones - Nicole L. Kinlock; Lisa Prowant; Emily M. Herstoff; Catherine M. Foley; Morodoluwa Akin‐Fajiye; Nicole Bender; Mihir Umarani; Hae Yeong Ryu; Bilgecan Şen; Jessica Gurevitch (Global Ecology and Biogeography, 2018)
Aim The pattern of increasing biological diversity from high latitudes to the equator [latitudinal diversity gradient (LDG)] has been recognized for > 200 years. Empirical studies have documented this pattern across many different organisms and locations. Our goal was to quantify the evidence for the global LDG and the associated spatial, taxonomic and environmental factors. We performed a meta‐analysis on a large number of individual LDGs that have been published in the 14 years since Hillebrand's ground‐breaking meta‐analysis of the LDG, using meta‐analysis and meta‐regression approaches largely new to the fields of ecology and biogeography. Location Global. Time period January 2003–September 2015. Major taxa studied Bacteria, protists, plants, fungi and animals. Methods We synthesized the outcomes of 389 individual cases of LDGs from 199 papers published since 2003, using hierarchical mixed‐effects meta‐analysis and multiple meta‐regression. Additionally, we re‐analysed Hillebrand's original dataset using modern methods. Results We confirmed the generality of the LDG, but found the pattern to be weaker than was found in Hillebrand's study. We identified previously unreported variation in LDG strength and slope across longitude, with evidence that the LDG is strongest in the Western Hemisphere. Locational characteristics, such as habitat and latitude range, contributed significantly to LDG strength, whereas organismal characteristics, including taxonomic group and trophic level, did not. Modern meta‐analytical models that incorporate hierarchical structure led to more conservative and sometimes contrasting effect size estimates relative to Hillebrand's initial analysis, whereas meta‐regression revealed underlying patterns in Hillebrand's dataset that were not apparent with a traditional analysis. Main conclusions We present evidence of global latitudinal, longitudinal and habitat‐based patterns in the LDG, which are apparent across both marine and terrestrial realms and over a broad taxonomic range of organisms, from bacteria to plants and vertebrates.

White matter hyperintensities correlate to cognition and fiber tract integrity in older adults with HIV - Christa Watson; Edgar Busovaca; Jessica M. Foley; I. Elaine Allen; Christopher G. Schwarz; Neda Jahanshad; Talia M. Nir; Pardis Esmaeili-Firidouni; Benedetta Milanini; Howard Rosen; Owen T. Carmichael; Paul M. Thompson; et al. (Journal of NeuroVirology, 2017)

A Metabolomic Approach to Identifying Chemical Mediators of Mammal–Plant Interactions - David J. Tucker; Ian Robert Wallis; Jessica M. Bolton; Karen J. Marsh; Adam A. Rosser; Ian M. Brereton; Dean Nicolle; William J. Foley (Journal of Chemical Ecology, 2010)

Functional Consequences of HIV-Associated Neuropsychological Impairment - Ashley A. Gorman; Jessica M. Foley; Mark L. Ettenhofer; Charles H. Hinkin; Wilfred G. van Gorp (Neuropsychology Review, 2009)

Ecological Example of Conditioned Flavor Aversion in Plant–Herbivore Interactions: Effect of Terpenes of Eucalyptus Leaves on Feeding by Common Ringtail and Brushtail Possums - Ivan R. Lawler; Jessica Stapley; William J. Foley; Bart M. Eschler (Journal of Chemical Ecology, 1999)